Examining the moderating role of childhood attachment for the relationship between child sexual abuse and adult attachment - Shen, Fei (Journal of family violence, 2024)
Purpose: Child sexual abuse (CSA) has short-term and long-term effects on survivors, but distress after the abuse varies widely and not all survivors show a significant degree of distress. Factors contributing to the variations of CSA outcomes need to be further investigated. The present study examines the moderating role of childhood attachment in the relationship between the experience of CSA and adult attachment, psychological distress, and self-esteem. Methods: Seven hundred and sixty-seven adults participated in this study, of which 427 (55.67%) reported a history of CSA. Participants were recruited from various social media websites (e.g., Facebook, Craigslist, discussion board, university announcement board). To examine the moderating role of childhood attachment between the experience of CSA and adult attachment, we conducted path analysis. Results: Childhood attachment significantly predicted adult attachment, psychological distress, and self-esteem in adulthood and moderated the relation between CSA and anxious adult attachment; CSA survivors with more secure childhood attachment were less likely to develop anxious attachment in adulthood. Additionally, CSA survivors reported less secure adult attachment, more psychological distress, and lower self-esteem than did individuals without a history of CSA. Furthermore, secure childhood attachment was significantly associated with secure adult attachment, lower levels of psychological distress, and higher levels of self-esteem. Conclusions: The results suggested that secure childhood attachment at least partially protected against negative long-term effects of CSA and fostered healthier intrapersonal and interpersonal adjustment in CSA survivors.